PEMBERDAYAAN KADER DALAM PEMANTAUAN PERTUMBUHAN, PERKEMBANGAN DAN GIZI PADA BALITA - Magfirah; Nora Veri; Emilda AS; Idwar; Keumalahayati (Poltekkes Kemenkes Mataram, 2025)
Cases of child growth retardation generally occur in around 5-10% of children. In addition to growth, malnutrition in toddlers is also a problem that must be addressed. Screening the development of toddlers is very important and must be carried out regularly. Nutrition and development are closely related. Malnutrition can cause developmental disorders. The aim of this community service activity is to improve knowledge and skills, as well as to assist cadres in monitoring the development and nutritional needs of toddlers. This activity will be carried out through training and assistance involving 10 posyandu cadres from partner villages. The partners in this activity are the Head of Paya Bujok Tunong Village, Langsa Baro District, Langsa City, and the target group is the cadres. The activity was held from 20 to 29 August 2025. The location of the activity was at the Geucik Gampong Paya Bujok Tunong office, Langsa Baro District, Langsa City. The activity included lectures, question and answer sessions, and simulations of child development monitoring using the Developmental Pre-Screening Questionnaire (KPSP) form. The community service activity method involved education, simulation, and mentoring. The areas of development assessed were gross motor skills, fine motor skills, speech/language, and socialisation/independence. The target group's knowledge of how to prevent malnutrition in toddlers was also assessed. The training activity lasted 2 days, and the mentoring lasted 1 week. Posyandu cadres who had received training showed increased knowledge of developmental monitoring and malnutrition prevention. The pre-test knowledge category was 60%. After the cadres were trained, their knowledge increased to 80%. The cadres' skills in monitoring toddler development before training were in the good category for 3 people (30%). After training, the good category increased to 80%.